AN ANALYSIS OF ENGLISH SUFFIXES IN TIME MAGAZINE’S THE END OF CASH - Alifia, Nasha; Hariani, Safitri (JOURNAL OF LANGUAGE, 2025)
This study examines derivational and inflectional suffixes in Time Magazine’s article The End of Cash. Using a descriptive qualitative approach based on Sugiyono (2013) and Fromkin, Rodman, & Hyams (2010), the analysis identifies the types and frequencies of English suffixes in the text. The findings reveal 94 occurrences: 66 inflectional and 28 derivational suffixes. The most frequent inflectional suffixes are the plural -s and the progressive -ing, while the most common derivational processes include verb-to-noun and adjective-to-adverb transformations. Both of these types are the category of inflection which was found each of them as many as 21 words. While the the most frequent type of derivation is verb to noun and adjective to adverb. It was found each of them in 8 words using derivational suffixes -or, -sion, -ally, -or, -y, -ly, -ment, and-ist. The findings reveal 94 occurrences: 66 inflectional and 28 derivational suffixes. The most frequent inflectional suffixes are the plural -s and the progressive -ing, while the most common derivational processes include verb-to-noun and adjective-to-adverb transformations. These findings contribute to morphological studies by demonstrating how affixation operates in journalistic English and how it supports vocabulary development for EFL learners.